FACTORS AFFECTING THE DEVELOPMENT OF CAPACITY ORGANIZATION OF EXPERIENCE ACTIVITIES FOR STUDENTS OF PARTNERAL EDUCATION TAN TRAO UNIVERSITY - Hà Mỹ, Hạnh (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2021)
This study is conducted to indicate the theoretical and practical basis of the influence of these factors on the development of the competency to organize creative experience activities for students in primary education at Tan University. The results of data analysis show that the most influencing factor is student activeness; Teaching competency , the competency of teachers to organize experience activities. Other factors such as facilities, learning materials; time; coordination among educational forces… has also had a lesser effect.